Anti-microfouling Activity of Glycomyces sediminimaris UTMC 2460 on Dominant Fouling Bacteria of Iran Marine Habitats - Heidarian, Sheida; Mohammadipanah, Fatemeh; Maghsoudlou, Abdolvahab; Dashti, Yousef; Challis, Gregory L. (Frontiers in Microbiology, 2019)
Discovery of environmentally safe agents is currently of considerable interest, due to the continuous impacts of biofoulers on the marine habitats and the adverse effects of biocides on the environment. This study reports the anti-adhesion effect of marine living Actinobacteria against fouling strains isolated from submerged panels in marine environments of Iran. The extract of Glycomyces sediminimaris affected the biofilm formation of Kocuria sp. and Mesorhizibium sp., as the dominant fouling agents in this ecosystem, up to 93.2% and 71.4%, respectively. The metabolic activity of the fouler bacteria was reduced by the extract up to 17 and 9%, respectively. This indicated the bactericidal potency of the extract on cells in the biofilm state that enable the compound to be effective even once the biofilms are established in addition to the inhibition of biofilm initiation. Moreover, EPS production by fouling bacteria was reduced by 60-70%. The absence of activities against fouling bacteria in suspension and also the absence of toxic effect on Artemia salina showed the harmless ecological effect of the anti-microfouling extract on the prokaryotic and eukaryotic microflora of the studied Iran marine ecosystem. Metabolic profiling of Glycomyces sediminimaris revealed the presence of compounds with molecular formulae matching those of known anti-fouling diketopiperazines as major components of the extract. These results suggest that the extract of Glycomyces sediminimaris could be used as a potentially eco-friendly viable candidate in comparison to the synthetic common commercial anti-microfouling material to prevent the fouling process in marine habitats of Iran.